Intelligent street lighting energy-saving system based on climate conditions and vehicle’s movements - Al-Smadi, Adnan; Salah, Salam; Al-Momani, Areen; Al-Bataineh, Majd (Penerbit Universiti Kebangsaan Malaysia, 2021)
The huge amount of electric power and cost associated with street lighting has raised the need to investigate both cost issues and environmental concerns. Cities worldwide are increasingly investing in energy-efficient street lighting systems. Modern street lighting technology can lower energy consumption as well as operation and maintenance costs significantly. In addition, bright street lighting can reduce accidents and crime rate in the area. Street lighting is an essential public service that provides a significant factor contributing to the quality of life and productivity of people workforces. This paper proposes an intelligent and energy-efficient traffic sensing system based on the widely distributed street lights. It is intended to observe vehicle’s movement on the road and turn ON a block of street lights ahead of vehicle whenever needed. As the vehicle passes by, the system turns OFF the trailing lights. The brightness (intensity of light) of the street light is adjusted based on the surrounding using LDR sensor. Hence, the street lights will be switched ON in the evening around sunset when a vehicle passes by, and switched OFF in the morning after sunrise when there is sufficient light on the streets. In addition, the proposed system will control the intensity level of the street light using the LDR sensor. The Proteus Software Simulation of the proposed system was performed and tested. Then a hardware prototype was designed and implemented to evaluate the performance of the proposed system. This technology can save significant costs and energy.